SOFT GRAPHS OF THE BARBELL STAR GRAPH - Helmi, Monika Rianti; Sy, Syafrizal; Nazra, Admi; Muhafzan; Hanifa, Nurul; Alfiany, Noverina (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2025)
Let G^*=(V(G^*),E(G^*)) is a simple graph and A be a non-empty set of parameter. Let RA× V(G^*) be a arbitrary relation from A to V(G^*). A mapping F:A→ P(V(G^*)) can be defined as F(x)={yVxRy } and a mapping K:A→ P(E(G^*)) can be defined as K(x)={uvE{u,v}F(x)}. A pair (F,A) and (K,A) are soft sets over V(G^*) and E(G^*) respectively, then (F(a),K(a)) is a subgraph of G^*. The 4-tuple G=(G^*,F,K,A) is called a soft graph of G. In this paper, we enumerate soft graph of amalgamation of path and star.